2010
DOI: 10.3109/02699050903512863
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of cognitive retraining to neurological patients’ driving status: The role of process variables and compensation training

Abstract: Cognitive retraining exercises that incorporate skill remediation, 'process' variables and metacognitive skills, as well as a better WA with patients, positively related to clearance to drive at the time of discharge from a holistic milieu-oriented programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
1
22
0
1
Order By: Relevance
“…An earlier study from our center (3) reported that individuals who returned to driving differed significantly on treatment variables, performance on cognitive retraining tasks, as well as process variables such as working alliance and compensation use. With a better understanding of baseline assessment and recovery patterns, it may be possible to predict the ability to drive much earlier in the treatment process.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…An earlier study from our center (3) reported that individuals who returned to driving differed significantly on treatment variables, performance on cognitive retraining tasks, as well as process variables such as working alliance and compensation use. With a better understanding of baseline assessment and recovery patterns, it may be possible to predict the ability to drive much earlier in the treatment process.…”
Section: Discussionmentioning
confidence: 93%
“…The role of these functions in driving has been well documented in the literature (6, 9). Previous studies have reported the efficacy of cognitive measures, particularly those related to speed of information processing, visual scanning, and motor speed in predicting driving status (3, 26). DSC was one of the neuropsychological variables that contributed to discriminate 94.4% of competent drivers from non-competent drivers (26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations